Error Analysis of Junior High School Students on Linear Equations of Two Variables Topic - Pujiono; Boyke H Siahaan; Heddy Rosida (Universal Education Jurnal Teaching and Learning, 2024)
Mathematics is an important science and has a lot to do with the development of other sciences. One of the essential topics in physics is linear equations of two variables. However, many students experience errors on this topic. The purpose of this study is to identify students' errors on the material of linear equations of two variables. The research is a descriptive study conducted on 83 students at SMPN 1 Tanjung Jabung Barat. The instrument used in this question is five description questions. This question has been validated and tested empirically. The five questions are suitable for research. The data analysis technique used in this research is descriptive analysis. The results showed that students made many errors in operations, concepts, and skills.